2021
DOI: 10.21203/rs.3.rs-990324/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anemia Requiring Transfusion in Breast Cancer Patients on Dose-dense Chemotherapy: Prevalence, Risk Factors, Cost and Effect on Disease Outcome.

Abstract: Purpose: Dose dense chemotherapy improves survival but also increases toxicity and treatment related cost. Here we report the prevalence of anemia, understand the risk factors of chemotherapy related anemia and determine the cost and time-delay associated with transfusion requirement in Indian non-metastatic breast cancer patients on dose dense preoperative chemotherapy.Methods: In this study, 116 triple negative breast cancer (TNBC) patients were treated preoperatively with Docetaxel and Cyclophosphamide alte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Even a higher prevalence rate, 68%, was reported from an intensive care unit (ICU) in United State (US) comprehensive cancer center (7). In India, Sharma et al (9) found that 46.7% of 116 women with breast cancer were detected to have mild to moderate anemia at baseline analysis; while, all these women (n=116) had developed anemia during the course of chemotherapy. In Saudi, the prevalence of anemia among 320 patients with solid cancer was 44.1% and patients with colorectal (56.8%) and female genital cancer (43.8%) demonstrated higher anemia prevalence (4).…”
Section: Introductionmentioning
confidence: 99%
“…Even a higher prevalence rate, 68%, was reported from an intensive care unit (ICU) in United State (US) comprehensive cancer center (7). In India, Sharma et al (9) found that 46.7% of 116 women with breast cancer were detected to have mild to moderate anemia at baseline analysis; while, all these women (n=116) had developed anemia during the course of chemotherapy. In Saudi, the prevalence of anemia among 320 patients with solid cancer was 44.1% and patients with colorectal (56.8%) and female genital cancer (43.8%) demonstrated higher anemia prevalence (4).…”
Section: Introductionmentioning
confidence: 99%